2001
DOI: 10.1103/physreve.63.026301
|View full text |Cite
|
Sign up to set email alerts
|

Sonoluminescence and phase diagrams of single bubbles at low dissolved air concentrations

Abstract: We studied experimentally the dependence of light emission and phase space boundaries of air bubbles in water on the level of degassing down to low partial pressures of 15 mmHg. We found that the maximum obtainable light intensity increased monotonically by lowering the concentration of dissolved air in water. We also present a new technique to obtain the acoustic pressure (P(a)) and ambient radius (R0) parameters, based on the information provided by the timing of the flashes in the acoustic cycle. Using this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Very recently, Simon et al (2001) confirmed that lightemitting bubbles follow the stable diffusive equilibrium curves based on argon concentration alone (see Fig. 34).…”
Section: Bubble Equilibria With Chemical Reactionsmentioning
confidence: 61%
See 1 more Smart Citation
“…Very recently, Simon et al (2001) confirmed that lightemitting bubbles follow the stable diffusive equilibrium curves based on argon concentration alone (see Fig. 34).…”
Section: Bubble Equilibria With Chemical Reactionsmentioning
confidence: 61%
“…IV.C). Experimental phase diagrams in the c ϱ and P a phase space can be found in Simon et al (2001).…”
Section: E Interplay Of Diffusive Equilibria and Shape Instabilitiesmentioning
confidence: 99%
“…To ensure the bubble stabilities by changing the pressure amplitude, the bubble initial radius is changed [52]. It should be realized that in each case an appropriate phase diagram is used [53,54]. The achieved theoretical results are shown in Figs.…”
Section: Numerical Resultsmentioning
confidence: 98%
“…In a previous study [16] we exploited this fact to develop a new technique to deduce P a , R 0 or R(t). Here we elaborate on our method in more detail, present its advantages and limitations and compare its results with Mie scattering.…”
Section: Introductionmentioning
confidence: 99%